Mechanical properties of pultruded Kenaf fibre-reinforced vinyl ester composites - Abd Manab, Mohd Fairuz (2016)
Pultrusion is one of the polymer composite fabrication processes employing the combination of pulling and extrusion processes. The composite profiles are obtained by pulling resin impregnated fibres through a series of heated dies. The ability of pultrusion technique that supports high volume of fibre fraction produces the high stiffness of the composite profile. There are many parameters such as filler loading,mold temperature and pulling speed to be considered and controlled during pultrusion process. In the research, the studies on the optimal parameters that influence the mechanical properties of pultruded kenaf composites revealed that the pulling speed has the highest influence in the fabrication process which is 49.3% of the contribution. The combination of the optimal parameters was obtained from Analysis of Variance (ANOVA) are pulling speed 0.4 m/min, gelation temperature 120oC, curing temperature 180oC and filler loading 30% of the weight. The investigation of the effect of filler loading on mechanical properties of pultruded kenaf composites shown the highest tensile strength was obtained when the filler loading reached at 50%, flexural strength at 30%, flexural modulus at 50% and compressive strength at 40%. The studies on the effect of gelation and curing temperatures shows the optimum tensile strength of gelation and curing temperatures were at 100oC and 140oC respectively,tensile modulus 80oC and 180oC respectively, flexural strength 100oC and 140oC,flexural modulus 120oC and 180oC and compressive strength at 120oC and 180oC respectively. The investigation of the effect of pulling speed on the mechanical properties of pultruded kenaf composites shows the optimal pulling speed for tensile strength and compressive strength is 0.3 m/min, tensile modulus 0.1 m/min, flexural strength 0.4, flexural modulus 0.2 m/min. The effect of filler loading, gelation and curing temperatures and pulling speed on tensile properties of composites was observed morphologically in the micrograph images of tensile fractured samples. Fibre wetting,fibre and matrix adhesion, the gaps within the samples and fibre breakages were among the phenomena occurring in the composites.